Pendampingan Taman Pendidikan Al-Qur’an (Tpq) Sebagai Pusat Pembentukan Akhlakul Karimah di TPQ Baitul Izzah Dusun Jorong Desa Sembalun Bumbung Kecamatan Sembalun NTB - usman, Arifin; Samsul Bahri; Toni Hidayat; Rizkika Alpiana; Sriati Wabatini; Siti Zaenab; Nur Pazilah; Sohratul Aini; Siti Aisyah; Sri Harmonika (KREASI : Jurnal Inovasi dan Pengabdian kepada Masyarakat, 2023)
Al-Qur'an Education Park (TPQ) as a center for the formation of akhlakul Karimah towards children is an important thing in society, more specifically those who do not study at Islamic boarding schools. The role of parents is very important in guiding and accompanying their children's growth and development, especially children who often play online games will damage their mindset and morals. TPQ is one of the right places to study religion from an early age, so that you can become a better person, with a Quranic spirit, to fortify yourself against the increasingly rapid technological developments. The purpose of this activity is first to provide guidance to children in Jorong Hamlet, Sembalun Bumbung Village, so that they are able to apply akhlakul karimah in their daily lives. Second, helping parents in educating their children, because there are those who don't obey their parents. Third, reviving TPQ that has died (no activities). The method of implementing the activity is the halaqoh and iqra' method. In this method the children will be grouped into several groups, namely the Banin 1, 2 and 3 groups and the Banat 1, 2 and 3 groups. Then the children who are beginners are in the iqra' group.